EFEKTIVITAS KARBON AKTIF JERAMI SEBAGAI ADSORBEN UNTUK MENURUNKAN KADAR MANGAN (Mn) AIR SUMUR GALI (Studi di Puskesmas Krian pada Ruang UGD Kabupaten Sidoarjo 2019) - Sari Putri Utami; Demes Nurmayanti; Marlik . (Poltekkes Kemenkes Surabaya, 2020)
The ground water used is dug well water. In order to meet health requirements it needs processing in quality. Some well water contains high minerals in the form of manganese, manganese content of more than 0.5 mg/L can interfere with human health, it is necessary to process the adsorption process. Straw as an adsorbent contains cellulose which can bind metal ions. The study aimed to determine the effectiveness of straw activated carbon as an adsorbent material in reducing manganese content in dug well water.This type of research is one group pretest-posttest design that compares the decrease in manganese levels before and after the adsorption process was carried out using adsorbent straw activated carbon. The study was carried out in 7 treatments with controls, and variations in the mass of activated carbon straw were 5 gr, 10 gr, 15 gr, 20 gr, 25 gr, 30 gr. The treatment was carried out 4 the results of the replication were examined in the Laboratory. Data analysis using One Way Anova test.The results showed that the adsorption of straw activated carbon could reduce manganese levels in well water digging the initial level 1.119 mg/L to 1.161 mg/L mass 0 gr, 1.127 mg/L mass 5 gr, 1.132 mg/L mass 10 gr, 0.984 mg/L mass of 15 gr, 0.972 mg/L mass of 20 gr, 0.977 mg/L mass of 25 gr, and 0.855 mg/L mass of 30 gr. Based on the results of the One Way Anova test and the LSD follow-up test obtained by the treatment group which has the greatest influence on the average in reducing the levels of manganese water in the well, namely the mass of 30 gr with an efficiency of 23.59%.It was concluded that the adsorption of straw activated carbon was able to reduce manganese (Mn) levels but was not yet effective. The mass that has a large influence on average in reducing manganese levels is 30 gr. Further research is needed to be able to achieve adsorption efficiency and find an effort to reduce turbidity in sample water after treatment and it is recommended to increase the mass variation of straw activated carbon. KEYWORDS : dug well water, manganese, straw activated carbon